Outsourcing Decisions in Pharmaceutical Industry: RBV and TCE Perspective - Gupta, Anudeep (2008)
Outsourcing is becoming an increasingly popular phenomenon amongst the companies in recent years. Taking an outsourcing decision is not easy for any company as there are various factors to be considered. Two most popular theories till date which contributed immensely for this decision are transaction cost economics and resource based view. Both of the theory focus on different aspects and contradict each other. I have tried to develop a relationship between these two to arrive at a decision. At the same time other factors like hidden costs, supply chain management have also been explored and their importance have been assed while making the decisions. On the other hand growth of outsourcing in Pharmaceutical sector has been substantial. Through this research I have tried to gain a deep insight of outsourcing decisions in Pharmaceutical sector considering the TCE and RBV approach.